Istota systemu zarządzania w procesie kształtowania i rozwoju organizacji - Skalik, Jan; Bełz, Grzegorz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The development of organization needs changes of previously applied management systems and their correct interpretation. Various concepts of management systems including a concept proposal elaborated by the taskforce of Department of Designing of Management Systems from Wrocław University of Economics and its contribution to diagnosing, designing and improvement of organization were depicted in this paper. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 17-26